First observation of the doubly charmed baryon Ξcc + - Mattson, M. (2002)
The first experimental evidence for one of the six predicted baryon states which contain two valence charmed quarks-the doubly charmed baryons. As such, there were many predictions of the masses and other properties of these states. The properties of doubly charmed baryons provide a new window into the structure of baryonic matter.